2001
DOI: 10.1002/oa.543
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological analysis of shell middens in the Beagle Channel, Tierra del Fuego Island

Abstract: An archaeological programme beginning in 1993, in the Beagle Channel, aims to describe the long-term record of maritime faunal exploitation, and relate it to the environmental record.Results from quantitative analysis of remains from a series of shell midden excavations indicate a remarkably stable and resilient marine biota over the last 6500 years. Only in the previous century have there been changes in fauna, which might correspond to recent global warming. Copyright

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 2 publications
2
25
0
8
Order By: Relevance
“…As many have commented before (Siegel-Causey & Lefèvre, 1989;Schiavini & Yorio, 1995;Raya Rey & Schiavini, 2000;Estevez et al, 2001), this finding reflects the current situation since this species is the most abundant of the five shags and cormorants known for southern South America. While intersite comparisons are difficult because of differing sampling and excavation methodologies, changes through time at the same site are meaningful.…”
Section: Temporal Patterns Of Biotic Changesupporting
confidence: 78%
See 1 more Smart Citation
“…As many have commented before (Siegel-Causey & Lefèvre, 1989;Schiavini & Yorio, 1995;Raya Rey & Schiavini, 2000;Estevez et al, 2001), this finding reflects the current situation since this species is the most abundant of the five shags and cormorants known for southern South America. While intersite comparisons are difficult because of differing sampling and excavation methodologies, changes through time at the same site are meaningful.…”
Section: Temporal Patterns Of Biotic Changesupporting
confidence: 78%
“…Their similarity in abundance profiles through time to Imperial Shags, which do breed in the region, suggests that presence of Antarctic and Imperial shags in Fuego-Patagonian middens is decoupled from their breeding status. Most studies have shown that Fuego-Patagonian middens represent year-round accumulations of bones of breeding and non-breeding birds alike (Lefèvre, 1989a(Lefèvre, , 1993b(Lefèvre, , 1997Estevez et al, 1995Estevez et al, , 2001Estevez & Martinez, 1997). Furthermore, other non-breeding bird species such as albatrosses and petrels have been recovered in large numbers from southern South America middens.…”
Section: Temporal Patterns Of Biotic Changementioning
confidence: 97%
“…This approach, while offering a great control of the archaeological stratigraphy directly in the field, also provides the ideal settings for the use and development of -high resolution‖ techniques, such as micromorphology, bioarchaeology and residue analysis. The research effort concentrated on three areas:  The development of new lines of research in the region, such as anthracology (Piqué, 1997), phytolith analysis ), archaeozoology (Estévez et al, 2001;Juan-Muns, 1992;Mameli and Estévez, 2005), micromorphology (Balbo et al 2010) and the recognition of spatial patterns (Wünsch et al, 1996;Vila et al, 2009). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“… The improvement of recovery techniques such as excavation methods and sampling strategies for ichthyological (Juan-Muns, 1992;Estévez et al, 2001) and malacological remains (Verdún, 2006), and phytoliths Zurro, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Como hemos explicado en otro trabajo (Estévez et al 1998), la división del trabajo VILA, A. y ESTÉVEZ, J.…”
Section: Necesidad De Control Social De La Reproducciónunclassified